An Implementation of a Transaction Model for Business Process Systems - O. Garcia, Marcela; R. Braghetto, Kelly; Pu, Calton; Ferreira, João E. (Journal of Information and Data Management, 2012)
Business process systems have received increased attention from research and industry communities specially in order to guarantee transaction properties. Despite of the significant efforts in new transactional models and software tools developed, the business processes still offer a scenario with several theorical and practical challenges. In this article, we present an implementation of a transaction model based on WED(Work, Event and Data)-flow approach. WED-flow combines the concepts of business step composition, advanced transaction models, events, and data states in order to provide transactional support for business process systems. More concretely, our WED-flow implementation supports important aspects of business process systems such as: correct execution, integrity of business process instances in parallel execution, traceability, and recovery mechanisms.